2010
DOI: 10.1667/rr1910.1
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Recombination Contributes to the Repair of DNA Double-Strand Breaks Induced by High-Energy Iron Ions

Abstract: Zafar F., Seidler S.B., Kronenberg A., Schild D. and Wiese C. Homologous recombination contributes to the repair of DNA double-strand breaks induced by high-energy iron ions. Radiat. Res.To test the contribution of homologous recombinational repair (HRR) in repairing DNA damaged sites induced by high-energy iron ions, we used: 1) HRR-deficient rodent cells carrying a deletion in the RAD51D gene and 2) syngeneic human cells impaired for HRR by RAD51D or RAD51 knockdown using RNA interference. We show that in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 56 publications
5
59
0
Order By: Relevance
“…Interestingly, in an NHEJ-deficient genetic background, where HRR is the main mechanism for repair, the RBE for high LET radiation is close to 1 (6 -8), suggesting that HRR is not subject to inhibition by whatever mechanism interferes with NHEJ in high LETirradiated cells. This has been demonstrated in vivo (9) and confirmed by another group (10).…”
Section: Examples Of High Linear Energy Transfer (Let)supporting
confidence: 67%
See 1 more Smart Citation
“…Interestingly, in an NHEJ-deficient genetic background, where HRR is the main mechanism for repair, the RBE for high LET radiation is close to 1 (6 -8), suggesting that HRR is not subject to inhibition by whatever mechanism interferes with NHEJ in high LETirradiated cells. This has been demonstrated in vivo (9) and confirmed by another group (10).…”
Section: Examples Of High Linear Energy Transfer (Let)supporting
confidence: 67%
“…This conclusion has been verified by our group (8,9,36) and another group (10). The mechanism involves high LET IR-generated small DNA fragments (Յ40 bp) whose size prevents Ku from simultaneously binding to the two ends of one DNA fragment to initiate efficient NHEJ (8).…”
Section: Ape1 At Physiological Levels Contributes To High Let Ir-indumentioning
confidence: 60%
“…37 Complex DSBs are mainly repaired by the slow component, 27,35 which in G2-phase represents resection-dependent HR. 27,38 Recent data on the repair of covalently blocked DSB ends or IR-induced DSBs in DT40 B cells suggest a function of CtIP and MRE11 also in G1. 17,19 This is in line with the observed recruitment of RPA to complex DSBs in G1 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Zafar et al tested the contribution of homologous recombination pathway to repair DNA DSB induced by high LET radiation using RAD51D-deficient CHO cells and found that rad51d −/− cells are more sensitive than wild type CHO cells [103]. Moreover, studies of ataxia telangiectasia-mutated (ATM) protein, functioning upstream of both NHEJ and HR repair pathways, with ATM deficient cells and ATM inhibitors have also shown that lack of ATM significantly reduced cell survival after treatment with high LET carbon ion radiation [54,104].…”
Section: Dna Dsb Repair After High Let Radiationmentioning
confidence: 99%